Experiencing art together: integrating affect and semiosis - Schino, Gemma; van Klaveren, Lisa-Maria; van Dorsten, Theisje; Pathare, Samrddhee; van Heusden, Barend; Cox, Ralf F. A. (Frontiers in Psychology, 2025)
IntroductionArt is ubiquitous in our lives, and its experience and understanding are deeply emotional. Dewey suggested that all human experience, including art experiences, emerges from active engagement with the environment. In this view, affect and interpretation are interconnected processes that unfold together. To examine the integration of these processes, this interdisciplinary study used a multi-method approach.MethodsEighteen dyads of adult participants took part in the study. They were instructed to each bring an art object that was meaningful to them. During the experiment participants engaged in an audio-visually recorded, semi-structured conversation, reflecting on both art objects. They also answered pre- and post-questionnaires on their emotions. Affect was measured through self-reported valence and arousal of emotions, and sentiment analysis of the conversation. Semiosis as the process of making sense of the art objects was operationalized in terms of four strategies, namely: perception, imagination, conceptualization, and analysis. Affect was measured through self-reported valence and arousal of emotions, and sentiment analysis of the conversation.Results and discussionThe results showed that dyadic interactions led to changes, at the group level, in participants’ self-reported affect toward the other’s art object. An Exploratory Graph Analysis revealed unique weighted networks of sentiment for each strategy. Additionally, a Multinomial Log-linear Model demonstrated that affect and strategies work in tandem during the art experience, to predict perceived affect.